Assessing the Factor Structure and Measurement Invariance of the Test of Emotion Comprehension (TEC): A Large Cross-Sectional Study with Children Aged 3-10 Years. Issue 3 (26th May 2020) - Cavioni, Valeria; Grazzani, Ilaria; Ornaghi, Veronica; Pepe, Alessandro; Pons, Francisco
ABSTRACT: The Test of Emotion Comprehension (TEC) has been used extensively to investigate children's understanding of emotion. The present study aimed at investigating the TEC's factorial structure, its measurement invariance across age and gender, and defining age-referred TEC scores, in a large sample of 1, 478 children (755 males, 723 females) aged between 3 and 10 years. Confirmatory factor analysis of the data yielded support for the original psychometric structure of the TEC, which is based on three developmental domains of emotion understanding: external, mental, and reflective. Measurement equivalence was supported across age and gender groups. We also obtained normative data for interpreting TEC outcomes and defined the corresponding normative pattern of development across six-month age intervals. Overall, our findings suggest that the TEC is a robust instrument for investigating emotion understanding in children aged 3 to 10 years. The limitations of the study and the potential use of the TEC are discussed.